Sistema de Medição Precisa do Consumo de Energia em Dispositivos Móveis de Comunicação Sem Fio - Monteiro, Alexandre Coser; Vianna, Ricardo Guerra; Dutra, Renato de Castro; Branco, Luiz Maltar Castello; Amorim, Claudio Luis de (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2007)
The battery time life of mobile wireless equipments such as palmtops, laptops, and celulars, depends strongly on the efficiency of their wireless communication devices to save energy when in operation. In this article, we describe the design of a new electronic device capable of measuring the energy cost of basic wireless communication events, including scan, connection, and data transport. We illustrate the potentials of our equipment by fine measuring the energy costs of the Bluetooth protocol operation in practical situations.